A study on compressive strength of concrete with glass aggregate / Scott Simon Bosuin - Bosuin, Scott Simon (2005)
A study on compressive strength of concrete with glass aggregate will be carried out. In this study, the potential of glass waste aggregate as a replacement to the normal aggregate will be investigated. The waste glass, which is broken or rejected during the process of recycling, has a potential to be used as a glass aggregate. By using glass aggregate, the environmental problem can be reduced and provide an alternative for usage of normal aggregate. Generally, glass aggregate is clean, safe, economic, durable, strong and more workable. It can be used as a road beds, pavement and parking lots, as well as for drainage medium, backfill or landscaping purposes. The compressive strength depends on types of glass, where the strength at 28 days for pub and club bottle achieves 91.6 % and for bottle-bank achieves 81.8 % of relative strength. The size of the glass aggregate used in this study is 10.0mm. The type of glass is pub and club waste bottle. The grade of concrete is 30 and the replacements of the glass aggregate are 0%, 10%, 20%, 30% and 100%. The compressive strength of concrete cube will be tested on day 3, day 7, day 14 and day 28. For the preliminary study, a compressive strength test for concrete grade 30 has been carried out by using 100% glass aggregate to replace a normal aggregate. It is shown that, the compressive strength of concrete with glass aggregate is less compared to concrete with normal aggregate.